TRANSLATION QUALITY OF BILINGUAL NEWS “VAKSIN PALSU ANCAM ANAK INDONESIA JADI SOROTAN MEDIA ASING” BY NOVITA CAHYADI ON B2B NEWS SITE - Eka Yunita Liambo; Taufiq Jati Murtaya; Ika Oktaviana (LEAD (Language, Education and Development), 2023)
This study aims to find the translation quality of a news on B2B site. This study was qualitative descriptive research. The data were two news articles which are an article entitled “Vaksin Palsu Ancam Anak Indonesia Jadi Sorotan Media Asing” by Ismail Gani and translated news article entitled “Parents Told to Contact Doctors Amid Indonesia Vaccine Scandal” by Novita Cahyadi published in B2B (Berita 2 Bahasa) news website. The analysis of this study was based on three aspect of translation quality proposed by Larson which are accuracy, clarity, and naturality. The result of data analysis was that the there were several inaccuracies in the translation that interfere with the overall meaning. The clarity of the translation was considered good and the text was easily read by the reader since the absence of ambiguous or unclear words in the translated text. Whereas, the lack of quality was found in naturality aspect. The translated text had grammatical errors since it applies inappropriate tenses in the target language. However, the translation quality was considered good. Keywords: Translation Quality, News Translation, Bilingual Text,